Local management of national cluster policies: Comparative case studies of Japanese, German, and French biotechnology clusters - Hiroyuki Okamuro; Junichi Nishimura (Administrative Sciences, 2015)
Cluster policies have attracted increasing attention worldwide, but only a few studies have focused on their management by local cluster organizations. We investigate the relationship between national cluster policies and their management by local cluster organizations from a comparative perspective. For this purpose, we provide a detailed comparison of national cluster policies in Japan, Germany, and France as well as six prominent biotechnology clusters in these countries. Information on the focal clusters and on the management of cluster policies was obtained using semi-structured interviews with cluster managers. We find that national cluster policies considerably differ among these countries according to basic conditions of clusters and that the patterns of national cluster policy are closely related to those of local cluster management, despite some differences between clusters in the same country caused by various regional characteristics.
Keywords: 350; cluster policy; cluster organization; biotechnology; case study; international comparison; Japan; Germany; France